(7t-2) - (-3t+1) = -3*(1-3t)
First distribute:
7t-2+3t-1 = -3+9t
Now get all the terms with 't' on the same side by subtracting/adding:
7t+3t-9t = -3+2+1
Combine the terms:
1t=0
t=0
Check:
Plug in 0 for t and see if both sides of the equation come out the same:
Does (7(0)-2) - (-3(0)+1) = -3(1-3(0)) ?
(-2) - (1) = -3(1) ?
-3 = -3 ?
Yes! It works, so t=0!
K = ln (153/147)/7
k =
<span>
ln
(<span>
<span>
1.0408163265)/7
k = </span></span></span>0.040005334584
y(t) = a * e ^ k*t
y(2017) = 147 * e^ <span><span><span>0.040005334584
</span>
</span>
</span>
* 26
y(2017) = 147*e^
<span>
<span>
<span>
1.0401386992
</span>
</span>
</span>
y(2017) = 147*
<span>
<span>
<span>
2.8296094512
</span>
</span>
</span>
<span>y(2017) = 415.95 NOT very sure of that answer
</span>
Answer:
11
Step-by-step explanation:
1st plug in the given numbers for each variable (the letters)
4 x 6 ÷ 3 + 3 =
Next, use the order of operations to solve the expression.
4 x 6 ÷ 3 + 3 =
24 ÷ 3 + 3 =
8 + 3 = 11